Case report on visceral manipulation in adolescent idiopathic scoliosis - Chahab, Doctor in Osteopathy, Matias; Donnet, Osteopath, Pamela; Hernandez, Physical Therapist, Daniel (International Journal of Therapeutic Massage & Bodywork, 2022)
Introduction: Adolescent idiopathic scoliosis (AIS) is a deformity that affects the spine in three dimensions. Even though AIS patients are usually asymptomatic, AIS negatively impacts them, affecting their quality of life and restricting their social life. There are many treatment options but no gold standard. Visceral manipulation (VM) is widely used in osteopathic practice for the treatment of several conditions, but it is little known among the medical community. To the best of our knowledge, there are no scientific studies reporting VM as a treatment alternative for AIS. Case Presentation: The case was a 14-year-old girl with AIS (baseline Cobb angle of 38.9° in the lumbar spine and 32.3°in the thoracic spine). Although the patient had no physical symptoms, she was recommended for surgery to correct the deformity. The osteopathic assessment indicated that the uterus and pericardium where the main anatomical structures creating tension. Two VM sessions were conducted with a month-and-a-half interval between sessions. The follow-up X-ray revealed a Cobb angle of 32.1° in the lumbar curvature and 34.3° in the thoracic curvature. The results were perceived as an improvement by the patient and her parents. No adverse events or complications were reported. Discussion: After two session of visceral osteopathic treatment, this document reports a 6.8° Cobb angle reduction of the primary curve in a patient with AIS, with the thoracic curvature becoming the major curve.